Household Income and Older Adult Population Predict Number of Integrative Medicine Providers Around US Hospitals: An Environmental Scan Study. (10th August 2022) - Hill, Jacob D.; Schmucker, Abigail M.; Siman, Nina; Goldfeld, Keith S.; Cuthel, Allison M.; Adeyemi, Oluwaseun J.; Edwards, Eliot; Bouillon-Minois, Jean-Baptiste; Grudzen, Corita R.
Background: Integrative medicine (IM) is a growing subspecialty among the American healthcare system, but little is known about geographical and sociodemographic variability in access to services. Objective: To better understand access to IM healthcare services, we aim to: 1.) document the number of IM providers within the hospital service area (HSA) of various hospitals across the United States (US) and, 2.) explore the relationship between age, income, and race as predictors of the number of IM providers. Methods: We conducted an environmental scan to document the number of IM providers including naturopathic, acupuncture, chiropractic, and massage therapy providers within the HSA of 16 US hospitals using state and national search databases. We examined predictors of the number of providers per HSA using population and demographic data from the U.S. Census Bureau. Search database quality was evaluated using the Center for Disease Control and Prevention Clear Communication Index. Results: The number of IM providers varied from 11.6 – 67.4 providers/100, 000 persons. Massage therapists were the most prevalent (n = 13.8/100, 000), followed by chiropractors (n = 5.2/100, 000), acupuncturists (n = 4.6/100, 000), and naturopathic physicians (n = .5/100, 000). Higher average household income and population >65 years old were associated with more IM providers within an HSA (Rate Ratio (RR) 4.22, 95% CI 1.49-12.01; and 1.14, 1.05 - 1.24, respectively). In addition, the quality of publicly available search databases varied widely among US states (4.84 - 8.00/10), but less so among IM provider types (6.21 - 7.57/10). Conclusions: The high variability in number of IM providers and search database quality among various HSAs across the US warrants further investigation into factors influencing access to services. Our findings regarding income and older adult population raise concern for inequitable access to care, but are also promising when considering the increasing demand for healthcare services among the older adult population.